2016
DOI: 10.1001/jamaoto.2015.3370
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of the Supraglottis in Laryngomalacia With 3-Dimensional Pediatric Endoscopy

Abstract: The anatomy of the supraglottis in laryngomalacia is better visualized using 3D techniques. Use of 3D endoscopy may allow for more precise tissue removal. The outcomes and complication rates are similar to those of standard 2D techniques. This study provides a platform to begin comparative analysis between 3D and standard 2D techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…Comparisons between the two endoscopes (Table I) found no evidence of significant differences between the time (P = .153) or the adjustment time (P = .067), although the trend was for the latter to be longer in the 3D endoscopes irrespective of whether using this endoscope first or second. However, past pointing was found to be significantly lower when using 3D endoscopes (median 0 vs. 2, P = .025), and depth perception (8 vs. 4, P < .001) Adjustment Time (seconds) 9 (5-13) 10 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .067…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparisons between the two endoscopes (Table I) found no evidence of significant differences between the time (P = .153) or the adjustment time (P = .067), although the trend was for the latter to be longer in the 3D endoscopes irrespective of whether using this endoscope first or second. However, past pointing was found to be significantly lower when using 3D endoscopes (median 0 vs. 2, P = .025), and depth perception (8 vs. 4, P < .001) Adjustment Time (seconds) 9 (5-13) 10 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) .067…”
Section: Resultsmentioning
confidence: 99%
“…3D endoscopes have encountered an evolution of their own through improvements in image clarity and endoscopic quality. Recently, multiple studies have shown subjective improvements in precision of anatomy identification, stereoscopic depth perception, and surgical comfort . Despite this, there has been minimal objective data collection with small studies highlighting postoperative outcomes, length of hospital stay, quantity of blood loss, and complication rates comparable to standard 2D techniques .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations